Cytoprotective Effects of Fish Protein Hydrolysates against H2O2-Induced Oxidative Stress and Mycotoxins in Caco-2/TC7 Cells - Mercedes Taroncher; Yelko Rodríguez-Carrasco; Tone Aspevik; Katerina Kousoulaki; Francisco J. Barba; María-José Ruiz (MDPI AG, 2021)
Many studies report the potent antioxidant capacity for fish protein hydrolysates, including radical scavenging activity and inhibition ability on lipid peroxidation (LPO). In this study, the in vitro cytotoxicity of protein hydrolysates from different salmon, mackerel, and herring side streams fractions was evaluated in the concentration range from 1 to 1:32 dilution, using cloned human colon adenocarcinoma cells TC7 (Caco-2/TC7) by MTT and PT assays. The protein hydrolysates' antioxidant capacity and oxidative stress effects were evaluated by LPO and reactive oxygen species (ROS) generation, respectively. The antioxidant capacity for pure and bioavailable hydrolysate fraction was also evaluated and compared. Additionally, mycotoxin levels were determined in the fish protein hydrolysates, and their cytoprotective effect against T-2 toxin was evaluated. Both hydrolysates and their bioavailable fraction induced similar cell viability rates. The highest cytoprotective effect was obtained for the salmon viscera protein hydrolysate (HSV), which increased the cell viability by 51.2%. ROS accumulation induced by H2O2 and LPO was suppressed by all pure hydrolysates. The cytoprotective effect of hydrolysates was observed against T-2. Moreover, the different fish fraction protein hydrolysates contain variable nutrients and unique bioactive peptide composition showing variable bioactivity, which could be a useful tool in developing dietary supplements with different target functional properties.